МОНГОЛ УЛСЫН ИХ ХУРЛЫН ГИШҮҮНИЙГ СОНГОГЧДЫН САНАЛААР ЭГҮҮЛЭН ТАТАХ ЭРХ ЗҮЙН ОРЧНЫГ БҮРДҮҮЛЭХ АСУУДАЛД - Ц.Ганболд; С.Жавхлан (Politology, 2023)
In an effort to improve discipline and accountability of elected members of the Mongolian parliament, calls for legislative recall mechanisms have gained momentum in recent years. Though such practice is fairly uncommon, the notion of creating a mechanism which would allow voters to be able to exercise control over elected officials and hold those who have failed to represent their constituents' best interests accountable has become increasingly popular. This paper aims to highlight key factors to be taken into consideration if such a procedure is to be legislated.